ENHANCING SUSTAINABLE PRACTICES: STAKEHOLDER ENGAGEMENT IN CORPORATE SOCIAL RESPONSIBILITY - Dr. D. P. Dewangan Dr Ramesh Kumar Pandey, (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The research explores the imperative of stakeholder engagement in fostering corporate social responsibility (CSR) and enhancing sustainable practices within organizations. Recognizing the multifaceted nature of sustainability, this paper underscores the pivotal role of stakeholders in driving CSR initiatives and achieving long-term sustainability goals. Through a comprehensive review of existing literature and case studies, the abstract elucidates the benefits of proactive stakeholder engagement, including improved organizational legitimacy, enhanced reputation, and strengthened relationships with key stakeholders. It examines various strategies and approaches for effective stakeholder engagement, such as dialogue, partnership building, and transparency in decision-making processes. The research also emphasizes the importance of integrating stakeholder perspectives into CSR strategies to ensure alignment with societal needs and expectations. By fostering collaboration and co-creation with stakeholders, organizations can navigate complex sustainability challenges, mitigate risks, and seize opportunities for innovation and value creation. This research advocates for a holistic approach to CSR that prioritizes stakeholder engagement as a cornerstone for building resilient, responsible, and sustainable businesses.